A Study on Challenges of Border Management System along the Indo-Nepal Border (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
The Indo-Nepal border, stretching over 1,808 kilometres, is defined by an open border system that permits the free movement of people and goods between Nepal and India, a system formalized through the Nepal-India Peace and Friendship Treaty of 1950. This arrangement has fostered strong historical, cultural, and economic ties, facilitating labour mobility, trade, and tourism. However, the open border has also introduced significant security challenges, including illegal trafficking, human trafficking, smuggling, and potential exploitation by insurgent and terrorist groups. This study examines the prospects and problems associated with the open border between Nepal and India, with a focus on the security risks it poses to Nepal. Utilizing a qualitative research methodology, the study draws on secondary data sources such as books, reports, journal articles, and expert opinions to explore the complexities of border management in the contemporary security environment. The research adopts the Three Horizons Model framework, which explores the present challenges, anticipates emerging threats, and formulates strategic responses for future border security management. By identifying underlying security risks, the study aims to offer recommendations for enhancing border security measures. The findings contribute to regional security discourse and provide actionable insights for strengthening Nepal-India cooperation to mitigate vulnerabilities arising from the open border system.